Thoracic endografting for aortic occlusion after coarctation surgery - Meisenbacher, Katrin; Körfer, Daniel; Schmack, Bastian; Böckler, Dittmar; Bischoff, Moritz (Annals of vascular surgery, 2021)
Acute occlusion of the descending thoracic aorta (DTA) is rare and associated with high morbidity and mortality. In the case described here, rescue thoracic endovascular aortic repair (TEVAR) was successful in a 59-year-old man with acute occlusion of the DTA accompanied by lower body hypoperfusion after two previous open repairs for aortic coarctation.